Analisis Profil Kesehatan Calon Pengantin Perempuan - Utami, Kusniyati; Setyawati, Irni; Ariendha, Dian Soekmawaty Riezqy (Poltekkes Kemenkes Kupang, 2024)
Background: The health of female prospective brides is one of the most important factors in building a quality family. Premarital health examinations are crucial for detecting and addressing health issues before marriage. The aim of this study was to assess the health status of female prospective brides and analyze the relationship between relevant variables. Method: This was an analytical study with a cross-sectional design. The population consisted of 329 female prospective brides who visited X Primary Healthcare in Mataram between January and December 2022. A consecutive sampling method was used, with 267 participants involved. Results: The study found that most of the prospective brides were within the adult reproductive age range of 20-35 years (85%). The majority had a normal BMI (53%), did not suffer from Chronic Energy Deficiency (KEK) (79%), and more than half were not anemic (52%). Bivariate analysis revealed a significant relationship between BMI and Upper Arm Circumference (LILA) (p < 0.05). The Odds Ratio of 4.069 indicates that prospective brides with a low BMI were more likely to have a lower LILA.